Development of digital competences in the Bulgarian secondary school context–a literature review of good practices - Nikolova, Nikolina; Zafirova-Malcheva, Temenuzhka; Kirilova, Borislava; Mihnev, Pencho (Frontiers in Education, 2024)
The digital competence is one of the key competences needed for an active and fulfilling life. In the Bulgarian secondary schools, there are subjects dedicated to the development of digital competences: Computer modeling and information technologies (CMIT) in low secondary school, informatics and information technologies (IT) in upper secondary school. Partially, the process interweaves mathematics education, too. The focus of the study is to identify good practices for effective development of the digital competences of students in the context of Bulgarian formal education. An additional goal is to identify good practices in the professional development of teachers so that they can successfully develop the digital competences of their students. A systematic literature review is presented to achieve the objectives of the study. The identified teaching methods are classified according to the target groups and the digital competences they contribute to the development of. Finally, methods are outlined that should underpin the training of teachers so that they successfully develop digital competences of their students.